Spreading behavior of firefighting foam solutions on typical liquid fuel surfaces. Issue 6 (31st July 2022) - Sheng, Youjie; Li, Yang; Ma, Wenzhi; Zhang, Hanling
Abstract: A series of experiments was performed to investigate the spreading behavior of firefighting foam solutions on liquid fuel surfaces. The spreading coefficients of six kinds of aqueous film‐forming foam solutions and one fluorine‐free foam solution on the surface of four liquid fuels, namely, cyclohexane, diesel, n‐heptane, and ethanol, were calculated on the basis of surface and interfacial tension. Spreading behavior was studied systematically using a high‐speed camera, and then the relationship between spreading behavior and spreading coefficient was analyzed. Furthermore, the spreading area and spreading rate of different foam solution droplets on liquid fuel surfaces were studied in depth. The spreading amount of the foam solution droplets on the liquid fuel surfaces was measured. Four typical spreading phenomena, namely, spreading, suspension, dissolution, and sinking, of AFFF solutions on liquid fuel surfaces were identified. Moreover, a positive spreading coefficient did not necessarily lead to the formation of an aqueous film. The spreading area, spreading rate, and spreading amount were not proportional to the spreading coefficient. During the evaluation of the spreading property of firefighting foam, the spreading coefficient, spreading rate, and spreading amount must be focused on instead of only the spreading coefficient. Abstract :